Nowa międzynarodowa jednostka walutowa „prawo do specjalnego ciągnienia" MFW - Knakiewicz, Zenobia (Wydział Prawa i Administracji UAM, 1971)
The subject under consideration is the conception and significance of special drawing rights and the main reason for the introduction of the new international monetary unit. Also indicated is the fundamental difference between the drawing rights and the spacial drawing rights. To meet the need as and when it arises for supplement to existing reserve assets the Fund is authorized to allocate special drawing rights to members that are participants in the Special Drawing Account. The new international unit, commonly known as SDR (Special Drawing Rights) or gold paper was introduced in January 1970. It's parity is 0,88671 g of fine gold, thus equal to the US dollar. It is expressed in dollars but not US dollars. It is issued by the IMF. The grounds for issuing is mutual committance of the participants in the Special Drawing Account, to use the SDR as a means of payment in international settlement of payments. The introduction of SDR constitutes a further step in demonetization of gold, but does not yet mean its full demonetization. SDR is demonetized gold, despite its parity in gold. Here gold plays the role of a yardstick of international measure of values. The introduction of SDR has positive influence on international liquidity thanks to the possibility for supplement to existing reserve assets. Though reducing it does not however, eliminate all the difficulties of those countries which have a long-standing debit balance of payments.
The New International Unit: Special Drawing Rights in the International Monetary Fund